FOTODEGRADASI ZAT WARNA TEKSTIL CONGO RED DENGAN FOTOKATALIS ZnO-ARANG AKTIF DAN SINAR ULTRAVIOLET (UV) - Saraswati, I Gusti Ayu Adesia; Diantariani, Ni Putu; Suarya, Putu (Jurnal Kimia (Journal of Chemistry), 2015)
The research was conducted to study photodegradation of congo red textile dyes by using photocatalyst ZnO-activated carbon and UV light. The parameters observed were optimum quantity of the photocatalyst ZnO-activated carbon, optimum pH, optimum radiation time, reaction rate constant, and the effectivity of photodegradation congo red. Photocatalyst ZnO-activated carbon was synthesized using sol-gel method with the ratio of ZnO : activated carbon 5:1. The results showed that the optimum condition of photodegradation congo red required 50 mg of photocatalyst ZnO-activated carbon, pH 4, and 5 hours exposured to UV light radiation. The photodegradation rate constant of congo red using photocatalyst ZnO-activated carbon was 0.1745 hours -1 and without photocatalyst was 0.0200 hours -1 .  The photocatalyst ZnO-activated carbon in its optimum conditions was effective to reduce congo red textile dyes with 91.81 ± 1.24 percentages of degradation.
Keywords: Photodegradation, ZnO-activated carbon, photocatalyst, congo red